Managing talent : a critical appreciation - Swailes, Stephen (Talent management, 2020)
Managing Talent: A Critical Appreciation is aimed at management researchers seeking alternative and sometimes suppressed insights into talent theory and practice. The book gives alternative critical understandings of management innovations and highlight fresh insights into popular management ideas, practices and the literatures that surrounds them.